Transcriptome analysis of near‐isogenic lines provides molecular insights into starch biosynthesis in maize kernel. Issue 8 (8th April 2016) - Xiao, Yingni; Thatcher, Shawn; Wang, Min; Wang, Tingting; Beatty, Mary; Zastrow‐Hayes, Gina; Li, Lin; Li, Jiansheng; Li, Bailin; Yang, Xiaohong
Abstract: Starch is the major component in maize kernels, providing a stable carbohydrate source for humans and livestock as well as raw material for the biofuel industry. Increasing maize kernel starch content will help meet industry demands and has the potential to increase overall yields. We developed a pair of maize near‐isogenic lines (NILs) with different alleles for a starch quantitative trait locus on chromosome 3 ( qHS3 ), resulting in different kernel starch content. To investigate the candidate genes for qHS3 and elucidate their effects on starch metabolism, RNA‐Seq was performed for the developing kernels of the NILs at 14 and 21 d after pollination (DAP). Analysis of genomic and transcriptomic data identified 76 genes with nonsynonymous single nucleotide polymorphisms and 384 differentially expressed genes (DEGs) in the introgressed fragment, including a hexokinase gene, ZmHXK3a, which catalyzes the conversion of glucose to glucose‐6‐phosphate and may play a key role in starch metabolism. The expression pattern of all DEGs in starch metabolism shows that altered expression of the candidate genes for qHS3 promoted starch synthesis, with positive consequences for kernel starch content. These results expand the current understanding of starch biosynthesis and accumulation in maize kernels and provide potential candidate genes to increase starch content. Abstract : The transcriptomic variation of the developing kernels at 14 and 21 DAP was explored between a pair of maize near‐isogenic lines, which contains different alleles for a starch QTL on chromosome 3 ( qHS3 ). The result shows that the altered expression level of the candidate genes for qHS3 may promote starch synthesis, with positive consequences for starch content.